Effects of initial oxide layer on growth of titania nanotubes - Lim, Jonathan Jian Wei. (2011)
In this study, commercially obtained titanium foils were annealed first at different temperatures (i.e., 300°C, 400°C, 500°C, 600°C, 700°C, and 800°C) for a dwell duration of 10 min, or at same temperature of 400°C for different dwell durations (i.e., 10 min, 30 min, and 60 min), in order to form different oxide layers. The as-annealed titanium foils were then used to grow nanotubes to investigate the effect of original oxide layer on the growth of nanotubes. The initial oxide layer was discovered to perform as a protective layer against chemical dissolution for nanotube growth. Different annealing temperatures resulted in different phase compositions of the original oxide, and thus exhibiting different durability of chemical dissolution. The length of the nanotubes grown from the foils annealed at 300°C and 400°C was similar to that without annealing. The tube length declined when the foils were annealed at 500°C and 600°C, due to formation of the anatase structure, and increased again to the initial length level when being annealed at 700°C as a result of formation of rutile structure which was more stable as compared to the anatase phase. Finally, the tube length decreased drastically with the foils annealed at 800°C owing to the thick rutile oxide layer. Prolonged annealing duration at 400°C led to further crystallization of the annealed oxide layer from amorphous to anatase phase. This also resulted in different chemical dissolubility of the oxide layer.